2019
DOI: 10.1177/0958305x19881361
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap when implementing technologies intended to reduce or shift energy consumption in blocks-of-buildings

Abstract: If the designers of technologies intended to reduce or shift energy consumption are not sensitive to how people live and work in buildings, a gap occurs between the expected and actual performance of those technologies. This paper explores this problem using the concepts of ‘design logic’ (designers’ ideas, values, intentions and user representations) and the ‘user logic’ (related in this case to how building occupants currently live and work in a building). The research presented unpacks the ‘design logic’ em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The three readiness categories offer the possibility to assess beforehand what is needed for a good match between a DR solution and the specific site-in order to obtain insight in how DR or other energy-related services may be relevant for a specific BOB. As such, we have attempted to provide a tool for those interested in developing propositions offering energy optimization services that are in line with the customer and user needs [3], with the organizational ambitions and priorities at the BOB, the technical and physical starting situation and that offer possibilities to develop value in a functioning market context.…”
Section: Discussionmentioning
confidence: 99%
“…The three readiness categories offer the possibility to assess beforehand what is needed for a good match between a DR solution and the specific site-in order to obtain insight in how DR or other energy-related services may be relevant for a specific BOB. As such, we have attempted to provide a tool for those interested in developing propositions offering energy optimization services that are in line with the customer and user needs [3], with the organizational ambitions and priorities at the BOB, the technical and physical starting situation and that offer possibilities to develop value in a functioning market context.…”
Section: Discussionmentioning
confidence: 99%
“…As examples from other energy projects have shown, partnering with local community organisations and institutions [103], as well as engaging with the islanders with transparency in order to build trust [23] are crucial for the success of interventions for DR. Earlier research has also shown that if the designers of technologies intended to reduce or shift energy consumption are not sensitive to how people live and work in buildings, a gap occurs between the expected and actual performance of those technologies [104,105]. Therefore, it is essential to the success of SG interventions on islands that they are designed in ways which are sensitive to island residents' expectations.…”
Section: Observabilitymentioning
confidence: 99%
“…In order to control the peak load energy curves, some DR scenarios (three) had been applied. The demonstration scenarios represent a collection of ideas, views and assumptions about how DR-BoB can be achieved in buildings, to shift or to reduce energy demand [38]. Typically, the request to reduce demand is made for a specific time period on a specific day, which is referred to as a DR event [39].…”
Section: Dr Scenarios Implemented In Tucn Buildingsmentioning
confidence: 99%